2018
DOI: 10.17582/journal.aavs/2019/7.2.73.81
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological and Histochemical Postnatal Developmental Study of the Pelvic Reproductive Organs in Female Rabbits (Oryctolagus Cuniculus)

Abstract: This project was carried out to find out the structural histomorphological changes that take place in the pelvic parts (vagina and vestibule) of the female reproductive system of the rabbits (Oryctolagus Cuniculus) at three different postnatal periods of their life that were kitten, immature and mature does. To conduct such project, twenty four female rabbits were bought (8 for each age) from the local breeders. Rabbits were euthanized, dissected and subsequently vaginae and vestibules were collected and fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
2
8
1
Order By: Relevance
“…The vagina was characteristically very long tubelike organ in the studied guinea pig. It was entirely situated in the pelvic cavity running ventral to the rectum and such observations were in accordance with those described by (4) in the female bovine genital organ and vagina of the west african dwarf goat (17) and in the local does (18). The latter references also observed that the cranial end, the vagina was coiled around the Portio vaginalis of the cervix as a vagina fornix which gave rise to mucosal folds as recorded in the first cranial portion of guinea pigs vagina.…”
Section: A Grosslysupporting
confidence: 91%
See 3 more Smart Citations
“…The vagina was characteristically very long tubelike organ in the studied guinea pig. It was entirely situated in the pelvic cavity running ventral to the rectum and such observations were in accordance with those described by (4) in the female bovine genital organ and vagina of the west african dwarf goat (17) and in the local does (18). The latter references also observed that the cranial end, the vagina was coiled around the Portio vaginalis of the cervix as a vagina fornix which gave rise to mucosal folds as recorded in the first cranial portion of guinea pigs vagina.…”
Section: A Grosslysupporting
confidence: 91%
“…These findings were in a good agreement with previous researches stated that the lining epithelium of the cranial part of the vagina of adult animals was different than that of the caudal part (23). Differently, current findings were not comparable with those in female rabbits where the lining epithelium was ranged from simple columnar (cranially) to pseudostratified columnar or stratified squamous non keratinized (caudally) which gave negative reactions toward the histochemical staining procedures (18). Differently in guinea pigs vagina, the mucous cells were stained positively with histochemical stains such as PAS and AB (pH 2.5).…”
Section: B Microscopicallycontrasting
confidence: 87%
See 2 more Smart Citations
“…Due to their friendliness, ease of handling and observation, and the potential for breeding, rabbits were a frequent species used as an animal models in scientific research in human and animal medicine [ 1 – 3 ]. Rabbits are induced ovulators; therefore, pregnancy is particularly distinct, which is just hours or days after mating [ 4 , 5 ]. Receptive doe displays a larger number of ovarian follicles with an increased estrogen hormone level [ 6 ], resulting in reddish swollen vulva and lordosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%